Morphological and molecular variability of wild diploid and polyploid populations of Chrysolaena flexuosa (Sims) H. Rob: relevance for ornamental breeding - Echeverria, Maria Lis; Camadro, Elsa Lucila (Elsevier, 2021)
Chrysolaena flexuosa is a South American species of ornamental interest, whose variability has not been explored. The objective of this work was to perform joint analyses of morphological and molecular traits in seven accessions from its geographic distribution in Argentina: diploid, tetraploid and hexaploid, along an approximately 1400 km transect. To this end, 26 morphological traits were recorded in 10–24 plants/accession, and two combination of AFLP markers were used for molecular characterization. The data was subjected to multivariate and AMOVA analyses, and the genetic diversity among accessions was evaluated by using the Fst index. The multivariate analyses for morphological traits allowed the differentiation of groups that were in accordance with their geographical origin and, thus, their respective ploidies; with the diploids exhibiting smaller-sized organs but higher numbers of leaves and heads. In the AMOVA, differences between accessions according to geographic origin were not significant (p = 0.123), and the highest percentage of the molecular variance corresponded to intra-population variation (88.1%). The Fst index indicated moderate genetic differentiation among accessions (Fst = 0.11), as observed in other allogamous species as a consequence of inter-population gene flow. In turn, the detected variability for morphological traits of interest would allow the use of these accessions in ornamental breeding for cultivar development.